Avoiding Structural Collapse to Reduce Lead Leakage in Perovskite Photovoltaics. (5th May 2022) - Wei, Xueyuan; Xiao, Mengqi; Wang, Boyu; Wang, Chenyue; Li, Yuekang; Dou, Jing; Cui, Zhenhua; Dou, Jie; Wang, Hailiang; Ma, Sai; Zhu, Cheng; Yuan, Guizhou; et al.
Abstract: Perovskite solar cells (PSCs) have become a promising candidate for the next‐generation photovoltaic technologies. As an essential element for high‐efficiency PSCs however, the heavy metal Pb is soluble in water, causing a serious threat to the environment and human health. Due to the weak ionic bonding in three‐dimensional (3D) perovskites, drastic structure decomposition occurs when immersing the perovskite film in water, which accelerates the Pb leakage. By introducing the chemically stable Dion‐Jacobson (DJ) 2D perovskite at the 3D perovskite surface, the film dissolution is significantly slowed down, which retards lead leakage. As a result, the Pb contamination is dramatically reduced under various extreme conditions. In addition, the PSCs device deliver a power conversion efficiency (PCE) of 23.6 % and retain over 95 % of their initial PCE after the maximum power point tracking for over 1100 h. Abstract : Crystal structural collapse in perovskite films governs the Pb leakage after exposure to water as indicated by Noyes‐Whitney Model simulation. It is effectively retarded by constructing a chemically stable Dion‐Jacobson two‐dimensional (2D) perovskite (DOE)PbI4− x Cl x at the surface of the film.